38.6k views
5 votes
Two polynomials are given below

P =
3x^(2) + 2x - 6
Q =
2x^(2) - 2x + 10

Find p + q and q - p.
Show your work

User Amkhrjee
by
5.1k points

1 Answer

5 votes

Answer:

Note that P = 3x² + 2x - 6 & Q = 2x² - 2x + 10

Remember to combine terms only if they have the same amount of variables.

Q1: p + q

Plug in 3x² + 2x - 6 for p & 2x² - 2x + 10 for q:

p + q = (3x² + 2x - 6) + (2x² - 2x + 10) = 5x² + 0x + 4 = 5x² + 4

5x² + 4 is your answer.

Q2: q - p

Plug in 3x² + 2x - 6 for p & 2x² - 2x + 10 for q:

q - p = (2x² - 2x + 10) - (3x² + 2x - 6) = (2x² - 2x + 10) + (-3x² - 2x + 6) =

= -x² - 4x + 16

-x² - 4x + 16 is your answer.

~

User John Carrell
by
5.5k points